TINGKAT PARTISIPASI ANGGOTA TERHADAP KOPERASI UNIT DESA (KUD) MULIA DI DESA SARI MAKMUR KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Suharyanto Suharyanto; Rosnita Rosnita; Cepriadi Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to know the degree participant of member Mulia Coorporation in vilage Sari Makmur, Pangkalan Lesung in palelawan regency. This research used survey method.This research was using random sampling. The total sample thus research was 41 people. The sample found randomly from 500 mamber Mulia Coorporation. The colecting data of this research was using primary data and secondary data. To analize the degree and problems at participant of this research was using descritive method. To obtain the degree of participantion of getting result at meeting, implementation of participation in cooperation activities, participant to gain the function of service, and evalution of programs cooperation. The degree of members participation measured by using quisioner of likert scale the degree of members participant of members Mulia Cooperation in Sari Makmur , Pangkalan lesung, Pelalawan Regency was high with score 3,60 high of the degree participant on member Mulia Cooperation support by high partipant members on meeting, implemantion, service, also evolution program of cooperation. In another side the programs Mulia Cooperation in Sari makmur, Pangkalan Lesung, Pelalawan regencyhad some problems that related by the degree of participant were pasif on cooperation activities, attedenc, lack gave ideas on meeting, less armada dum truck, and participant on activiy and evolution of programs Mulia Cooperation.Keywords : The Degree of participant, peformace of Member, Cooperation, KUD Mulia